Evaluation of Annual Allowable Cut (AAC) Determination of Teak Forest Plantations in Perum Perhutani, Indonesia - Rohman Rohman; Sofyan P Warsito; Nunuk Supriyatno; Ris Hadi Purwanto; Catur Atmaji (Institut Pertanian Bogor (IPB University), 2014)
The degradation of teak forest plantations in Java that are managed by Perum Perhutani (PP) continues to happen, and this is caused by some risk factors such as illegal logging, grazing, forest fire, and encroachment. However, these risk factors have not been considered by PP notably in annual allowable cut (AAC) determination of yield regulation. Therefore, the AAC value could be overestimated. The research was aimed at evaluating the method of AAC determination and proposing an alternative method that considers the risk factors. This research was conducted with a series of data analysis approach from the data on five planning periods. The research result showed that forest damage occurs in varied situations. On average, the rate of deforestation accounted for 0.8% per annum. The calculation of AAC by considering the rate of damage risk in normal condition approximately made up 70.8%. Thus, compared to another method without considering damage risk rate, overestimation constituted 29.2%. In brief, this had an impact on the decline of timber stock.